Surgical Management of Cutaneous Nasal Sarcoidosis Involving the Alar Rim. (September 2015) - Melong, JC; Hart, RD; Trites, J; Taylor, SM
Systemic sarcoidosis is a granulomatous disorder that can affect multiple organs and tissues, resulting in varied clinical presentation. Head and neck manifestations are common and are often referred for appropriate diagnoses and management. Nasal cutaneous involvement, although an uncommon presentation, can result in nasal deformities and/or obstruction significantly impairing a patient's quality of life. Currently available pharmacological agents for the management of cutaneous sarcoidosis have yielded inconsistent results and, in the past, have been associated with disease relapse. Traditionally, surgery has largely been avoided because of the theoretical risk of disease flare-up. In the present report, the authors present a patient with atypical nasal cutaneous sarcoidosis involving the alar rim that was successfully managed with surgical intervention.